(untitled) (Jurnal Destinasi Pariwisata, 2025)
Strengthening community-based tourism (CBT) governance is an important strategy in the development of sustainable destinations, especially in ecologically vulnerable coastal areas. However, field practices often show a shift in power when formal actors take over management from pioneering communities, as seen in the Banua Pangka mangrove ecotourism destination, East Luwu. There is still limited understanding of how community exclusion occurs in the context of that institutional transition and how the community responds to it. This study shows that the dominance of formal institutions can lead to symbolic and procedural marginalization of the initiating community, but it also gives rise to adaptive strategies from the community to maintain its existence. This research uses an exploratory case study approach with a focus on a single coastal destination. Data were collected through semi-structured interviews, field observations, and local document analysis. The analysis was conducted thematically using NVivo software. The results show that there is a tension between the idealism of CBT and the reality of bureaucratization, which impacts participatory exclusion and decision-making disparities. On the other hand, the community was able to establish alternative business groups as a form of resistance and adaptive innovation. This study contributes to the development of more inclusive and adaptive tourism governance designs, and provides contextual lessons for policymakers and tourism industry actors in other coastal areas, particularly those characterized by marine ecotourism.